Analysis of the Causes of Defect and Proposed Improvements with Fault Tree Analysis Method in the Drawing Process at PT. XYZ - Yunita Nugrahaini Safrudin; Taufik Rahman (School of Industrial and System Engineering, Telkom University, 2021)
PT. XYZ is a manufacturing company that produces various types of metal-based products with a make toorder system. One of them is the Back Top Plate 450/456 (BTP 450/456) part which is a component ofrefrigerators. In the period of February-November 2020, PT. XYZ produces 15,395 units of BTP 450/456.However, BTP 450/456 products have the highest percentage of defective products. The average percentageof defective products is 3.06%, while the tolerance for the number of defects determined by the company is1%. This indicates a problem in the production process. The most types of defects in the production processof 450/456 are broken with a percentage of 41.88%. Based on Critical to Quality, the process stages that donot meet the requirements in the drawing process can cause various types of defects, such as wrinkles, breaks,miss-sizing, process failures, scratch and dents. The Fault Tree Analysis method is used to identify the rootcause of the type of broken defect. The root of these problems includes the absence of a guide for settingdies, the machine being operated for a long time, operator negligence, and the incorrect position of theplastic. The proposed improvement given are determining the optimal engine pressure, designing dies settingguides for operators, evaluating and improving the maintenance process, analyzing new machinerequirements, supervisors giving good directions to operators, periodic work evaluations to assess operatorperformance, designing visual displays as reminders for operators, and designing aids for positioning plasticson materials.